GENE-35. MGMT PROMOTER METHYLATION IN NEWLY DIAGNOSED LGG AS A POTENTIAL BIOMARKER FOR TMZ-ASSOCIATED HYPERMUTATION AT RECURRENCE. (11th November 2019) - Mathur, Radhika; Zhang, Yalan; Grimmer, Matthew; Hong, Chibo; Berger, Mitchel; Molinaro, Annette; Ann Oberheim-Bush, Nancy; Chang, Susan; Costello, Joseph
Abstract: Low-grade gliomas (LGGs), which include grade II astrocytoma and grade II oligodendroglioma, inevitably recur despite aggressive treatment with surgery, and sometimes, with radiation and the chemotherapeutic agent temozolomide (TMZ). The clinical benefit of TMZ in LGG is unclear, and a subset of TMZ-treated LGGs recur with hypermutation in association with malignant progression to high-grade tumors. It is currently unknown why some TMZ-treated LGGs recur with hypermutation while others do not. O6-methylguanine-DNA methyltransferase (MGMT) is a DNA repair protein that reverses mutagenic lesions induced by TMZ. The amount of MGMT protein in a cell is regulated at the epigenetic level by promoter methylation. Here, we hypothesize that epigenetic silencing of MGMT by promoter methylation facilitates TMZ-induced mutagenesis and contributes to the development of hypermutation. We demonstrate in a cohort of 37 TMZ-treated patients with an initial diagnosis of IDH -mutant LGG that methylation level of the MGMT promoter in initial untreated tumors is significantly associated with hypermutation at recurrence. We also confirm our previous finding that methylation level of the MGMT promoter in recurrent hypermutated tumors is higher than in recurrent tumors that are not hypermutated. These results provide a plausible mechanistic basis for observed differences in propensity of TMZ-treated LGG patients to develop hypermutation at recurrence. Furthermore, they establish the potential of MGMT promoter methylation level to inform treatment decisions in the clinic for patients with newly diagnosed LGG.